Study of the interaction of 2H-furo[3,2-b]pyran-2-ones with nitrogen-containing nucleophiles - Milyutin, Constantine V.; Komogortsev, Andrey N.; Lichitsky, Boris V. (Beilstein Journal of Organic Chemistry, 2025)
For the first time, the reaction of substituted 2H-furo[3,2-b]pyran-2-ones with diverse N-nucleophiles was investigated. It was shown that the direction of the process depends on the type of employed nitrogen-containing reagent. For example, condensation with aliphatic amines leads to 2H-furo[3,2-b]pyran-2,7(3H)-diones bearing an exocyclic enamine moiety. At the same time, interaction with dinucleophiles results in recyclization accompanied by opening of the furan ring. Relied on the aforementioned process a general method for the synthesis of substituted pyrazol-3-ones with allomaltol fragment was designed. Structures of representatives of all obtained products were unambiguously confirmed by X-ray diffraction.
Keywords: allomaltol; enamines; 2H-furo[3,2-b]pyran-2-ones; pyrazol-3-ones; recyclization